Correction: A conformational epitope in placental malaria vaccine antigen VAR2CSA: What does it teach us? - Justin Y A Doritchamou; Jonathan P Renn; Lars Hviid; Patrick E Duffy (PLoS Pathogens, 2024)
[This corrects the article DOI: 10.1371/journal.ppat.1011370.].